ROOT MERISTEM GROWTH FACTOR1 (RGF1)–RGF1 INSENSITIVE 1 peptide–receptor pair inhibits lateral root development via the MPK6–PUCHI module in Arabidopsis. (14th December 2022) - Jeon, Byeong Wook; Kim, Jin Sun; Oh, Eunkyoo; Kang, Na Young; Kim, Jungmook
Abstract: ROOT MERISTEM GROWTH FACTOR1 (RGF1) and its receptors RGF1 INSENSITIVEs (RGIs) regulate primary root meristem activity via a mitogen-activated protein kinase (MPK) signaling cascade in Arabidopsis. However, it is unknown how RGF1 regulates lateral root (LR) development. Here, we show that the RGF1–RGI1 peptide–receptor pair negatively regulates LR development via activation of PUCHI encoding AP2/EREBP. Exogenous RGF1 peptides inhibited LR development of the wild type. However, the rgi1 mutants were partially or fully insensitive to RGF1 during LR development, whereas four other rgi single mutants, namely rgi2, rgi3, rgi4, and rgi5, were sensitive to RGF1 in inhibiting LR formation. Consistent with this, the red fluorescent protein (RFP) signals driven by the RGF1 promoter were detected at stage I and the following stages, overlapping with RGI1 expression. PUCHI expression was significantly up-regulated by RGF1 but completely inhibited in rgi1 . LR development of puchi1-1 was insensitive to RGF1. PUCHI expression driven by the RGI1 promoter reduced LR density in both the wild type and rgi1, 2, 3 . Further, mpk6, but not mpk3, displayed significantly down-regulated PUCHI expression and insensitive LR development in response to RGF1. Collectively, these results suggest that the RGF1–RGI1 module negatively regulates LR development by activating PUCHI expression via MPK6. Abstract : The RGI1 receptor mainly transduces the RGF1 signal to activate expression of PUCHI, which can inhibit lateral root (LR) initiation and LR primordium development, via MPK6, negatively regulating LR formation.